Steroid therapy in extrahepatic cholestasis suggestive of biliary atresia: A case report - Syahbani, Primadita; Prihaningtyas, Rendi Aji; Setyoboedi, Bagus; Arief, Sjamsul (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Biliary atresia is a fibroinflammatory disease obstructing the extrahepatic biliary system. Biliary atresia is the leading cause of cholestasis in infants and the cause of end-stage liver disease in the first two years of life. Surgical treatment with Kasai portoenterostomy has been performed but has not eliminated the need for liver transplantation. The consideration of adjuvant steroid therapy for suppressing the fibro-inflammatory process in the bile ducts may improve the outcome of extrahepatic cholestasis. Case Presentation: A case of a 2-month 7-day-old boy with a chief complaint of jaundice with suspicion of biliary atresia. Jaundice started 1 week after birth, followed by acholic stools, yellow-brown urine, distended abdomen, hepatomegaly, and visible abdominal veins. Laboratory examination revealed an elevated level of direct bilirubin (cholestasis) in combination with elevated levels of aspartate aminotransferase (AST), alanine aminotransferase (ALT), and Gamma-glutamyl transferase (GGT), hypoalbuminemia, and reactive of IgG and IgM CMV. A percutaneous liver biopsy was performed and showed extrahepatic cholestasis with mild fibrosis consistent with biliary atresia. The patient was treated with oral methylprednisolone and ursodeoxycholic acid (UDCA). After 12 weeks of therapy, the patient was free of jaundice and darkening of stool color, followed by a normal bilirubin level. Conclusion: In young infants with extrahepatic cholestasis suggestive of biliary atresia, steroid administration resulted in clinical and laboratory improvement. The involvement of the immune response in the pathogenesis of biliary atresia may suggest new therapeutic targets for biliary atresia, such as steroids for improving the outcome of biliary atresia in young infants.